GENETIC TRANSFORMATION OF Melia azedarach L., USING Agrobacterium MEDIATED TRANSFORMATION - Nirsatmanto, Arif; Gyokusen, Koichiro (Secretariat of Forestry Research and Development Agency, 2007)
This study was subjected to observe the possibility of introducing specific foreign genes into Melia azedarach L., using Agrobacterium mediated transformation. Agrobacterium tumefaciens used in this study consisted of strains of EHA105 (vector plasmid pBIsGFP) and EHA105 (vector plasmid pBsGFP) to observe the possibility of introducing genes, and strains of EHA101 (vector plasmid pIG121-Hm) and LBA4404/ferritin (vector plasmid pBG-1) to observe the shoot organogenesis after genes transformation. Explants were collected from one cm in length excised stem of in-vitro plantlets. The results of the study showed that genetic transformations of M. azedarach could be potentially developed using Agrobacterium tumefaciens strains : EHA105 (pBIsGFP or pBsGFP), EHA101 (pGI121-Hm) and LBA4404/ferritin (pBG-1). The expression of GFP (green fluorescence protein) signal worked successfully in this transformation with 40% of transformation rate for pBIsGFP and 20 % for pBsGFP. The application of Agrobacterium strains of EHA101 (pIG121-Hm) and LBA4404/ferritin (pBG-1) which contained specific gene of kanamycin resistance and iron accumulation for plant growth improvement showed that adventitious shoot was well induced and elongated on the rate of 30 - 60 % of explants after genes transformation.